Minding their Ps and Qs; the Royal Navy purser and accounting and governance, 1731–1808. (August 2019) - McBride, Karen
This research explores the accounting regulations imposed on sea officers, particularly the purser, on board Royal Navy ships between 1731 and 1808. This was a period in which the Royal Navy grew to become one of the largest enterprises in Europe with operations throughout the world. The governance, control and accountability practices imposed upon pursers are analysed. The Regulations for accounting records to be kept by pursers indicate that accounting changed very little in the analysis period, until 1808, when it became substantially more detailed. Drawing on institutional theory, it is argued that this was due to external pressures for increased governance following the impeachment of Melville (First Lord of the Admiralty), public spending administrative and accounting reforms and political disapproval of 'offices of profit'. The article provides important insights to the development of accounting, governance, audit and accountability within the Royal Navy, and enhances understanding of the historically unique role of pursers.